2022
DOI: 10.1101/2022.10.26.513823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The function and decline of the female reproductive tract at single-cell resolution

Abstract: The female reproductive tract (FRT) undergoes extensive remodeling during each reproductive cycle, regulated by systemic changes in sex hormones. Whether this recurrent remodeling influences a specific organ's aging trajectory is unknown. To address this, we systematically characterized at single-cell resolution the morphological and transcriptional changes that occur in ovary, oviduct, uterus, cervix, and vagina at each phase of the mouse estrus cycle, during decidualization, and into aging. Transcriptional a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Fibrosis and inflammation are hallmarks of many aging tissues, and this is also true of the ovary which ages earlier relative to most organs [5, 10, 11, 15, 2022, 2427]. In this study, we advanced the field by demonstrating that we could mitigate age-related ovarian fibrosis through a systemic and constant administration of low dose Pirfenidone, an anti-fibrotic drug, for 6 weeks beginning in mice at 7 months of age when fibrotic foci are first observed in the ovary [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis and inflammation are hallmarks of many aging tissues, and this is also true of the ovary which ages earlier relative to most organs [5, 10, 11, 15, 2022, 2427]. In this study, we advanced the field by demonstrating that we could mitigate age-related ovarian fibrosis through a systemic and constant administration of low dose Pirfenidone, an anti-fibrotic drug, for 6 weeks beginning in mice at 7 months of age when fibrotic foci are first observed in the ovary [20].…”
Section: Discussionmentioning
confidence: 99%
“…We asked whether aging may also increase cell-to-cell variability in oocytes, as has been previously reported for other cell types. [85][86][87][88] We first compared gene expression variability by Shannon entropy between young and old oocytes (Figure 5D), and found that aging increases cell-to-cell variability. Similar analyses revealed that superovulation also substantially increases oocyte cell-cell variability in gene expression (Figure 5D).…”
Section: Granulosa Cell Markers Predict Oocyte Developmental Outcomementioning
confidence: 99%
“…Glandular offshoots (glandular epithelium) extending from the surface epithelium (luminal epithelium) project into the stroma and merge into a highly branched plexus running parallel to the myometrial border (Tempest et al 2020, Yamaguchi et al 2021. Recent single-cell transcriptomic approaches have revealed extensive heterogeneity among endometrial stromal and epithelial populations, illuminating the complexity of this important tissue (Garcia-Alonso et al 2021;Kirkwood et al 2021Kirkwood et al , 2022Wang et al 2020;Winkler et al 2022).…”
Section: Introductionmentioning
confidence: 99%